PENGARUH RASIONALITAS PENGGUNAAN ANTIBIOTIK TERHADAP PROGRAM PENGGUNAAN OBAT RASIONAL (POR) DI PUSKESMAS SAMBI REJO KABUPATEN LANGKAT TAHUN 2020 - Nurmayanti Nurmayanti; Selamat Ginting (Jurnal Penelitian Kesmasy, 2021)
Background: Rational drug selection is the key to quality health services. Improper use of antibiotics is one of the irrational uses of drugs and causes various health problems such as bacterial resistance and economic and social impacts. This study aimed to determine the pattern of antibiotic use against indicators of rational drug use in Sambi Rejo Public Health Center, Langkat Regency. Methods: The research method was carried out descriptively by retrospective data collection. Data on the use of antibiotics for the indicator of rational drug use is obtainable from the Rational Drug Use report data for the period January - December 2020, while data on pharmaceutical services was obtained in January - February 2021. The results of the study: The results showed that the use of antibiotics for indicators of rational drug use was Respiratory Tract Infection. The number of non-pneumonia was 28.33%, non-specific diarrhea was 46, 17 and the mean of drug items per prescription was 3.75 drug items. The results of research with in-depth interviews, participant observation and documentation study show that pharmaceutical services at the Sambi Rejo Health Center have been running quite well. The study concluded that pharmaceutical services at the Sambi Rejo Health Center have been running quite well, while the implementation of the rational drug use program at the Sambi Rejo Health Center has not been going well with the high use of antibiotics against indicators of rational drug use set by WHO.